2002
DOI: 10.1161/01.str.0000023576.94311.27
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Upper Airway Obstruction in the First 24 Hours After Acute Stroke

Abstract: Background and Purpose-The prevalence of sleep-disordered breathing after stroke has been reported to be between 32% and 71%. However, the first 24-hour period, when upper airway obstruction may have a critical effect on the cerebral circulation because of hemodynamic fluctuations and repetitive hypoxia, has not been studied. Furthermore, data on prediction of upper airway obstruction after stroke are limited. This study sought to assess the prevalence of upper airway obstruction in the first 24 hours of strok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(104 citation statements)
references
References 48 publications
5
93
1
4
Order By: Relevance
“…The left ventricular function was similar or higher in our series compared to previous studies [4,16] and may not explain the higher CPBS frequency found. Our patients were in part younger and had milder strokes compared to previous studies [4][5][6][7]11,12,16,24] and to a general stroke population [25,26] despite the absence of major differences in cardiovascular risk profile or stroke topography. However, considering that CPBS has been described in association with large and severe strokes [11,12], the younger age and the milder stroke severity are very unlikely to explain the higher CPBS frequency observed in our series.…”
Section: ) Frequency Of Cpbs In Acute Ischemic Strokementioning
confidence: 54%
See 1 more Smart Citation
“…The left ventricular function was similar or higher in our series compared to previous studies [4,16] and may not explain the higher CPBS frequency found. Our patients were in part younger and had milder strokes compared to previous studies [4][5][6][7]11,12,16,24] and to a general stroke population [25,26] despite the absence of major differences in cardiovascular risk profile or stroke topography. However, considering that CPBS has been described in association with large and severe strokes [11,12], the younger age and the milder stroke severity are very unlikely to explain the higher CPBS frequency observed in our series.…”
Section: ) Frequency Of Cpbs In Acute Ischemic Strokementioning
confidence: 54%
“…In previous studies investigating breathing disorders during sleep in the very early stroke phase (≤72 hours after stroke onset) performed with different portable devices [6,11,12,24] or with full polysomnography [7], CPBS was observed in 23-38% of patients [7,11,12,24], and was present during ≥10% of recording time in 12-28% of patients [6,24]. In contrast, in the studies performed with full polysomnography during the subacute stroke phase (after a mean time of 9 to 44 days after stroke) [4,5,16], lower frequencies of CPBS (6-19%) were reported.…”
Section: ) Frequency Of Cpbs In Acute Ischemic Strokementioning
confidence: 99%
“…204 Body position is important in interpreting polysomnographic findings after stroke because poststroke AHI often is highest when patients are maintained in the recumbent position, especially within the first 24 hours of stroke. 205,206 Bassetti and Aldrich 206 found an AHI Ն10 in 62% of transient ischemic attack patients compared with 12% of control subjects, suggesting that SDB may precede the onset of stroke. This was not confirmed in a case-control study of 86 transient ischemic attack patients, in whom the likelihood of sleep apnea was similar to that in control subjects.…”
Section: Strokementioning
confidence: 99%
“…it is in fact known that stroke can worsen breathing by a number of mechanisms, such as inducing swallowing abnormalities, narrowing of oro-and/or hypo pharynx, or hypomobility of ribcage. [24][25][26][27][28][29][30][31] Furthermore, individuals with severe oSah have higher loop-gain than those with milder oSah, 32,33 therefore their breathing during sleep can shift from oSah to cSah.…”
Section: Resultsmentioning
confidence: 99%